2016
DOI: 10.3174/ajnr.a4816
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Description of Brain Atrophy in Neuronal Ceroid Lipofuscinosis 2: Supratentorial Gray Matter Shows Uniform Disease Progression

Abstract: BACKGROUND AND PURPOSE:Experimental therapies for ceroid lipofuscinosis, neuronal, 2 (CLN2), a genetic disorder of childhood associated with progressive brain atrophy, are currently being developed. Because quantitative descriptions of the natural course of brain volume loss are needed to evaluate novel therapies, we performed MR imaging volumetry of patients with CLN2 to identify a suitable MR imaging marker of disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
5
16
1
Order By: Relevance
“…Grey matter volumes of treated patients decreased by 6.7% on average; however, volumetric changes were not recorded for historical controls. Nevertheless, this value is much lower than that reported from separate studies, which indicate an average loss of cortical volume of ~15–20% annually for patients with untreated CLN2 Batten disease 138 .…”
Section: Advances In Therapy Developmentcontrasting
confidence: 55%
“…Grey matter volumes of treated patients decreased by 6.7% on average; however, volumetric changes were not recorded for historical controls. Nevertheless, this value is much lower than that reported from separate studies, which indicate an average loss of cortical volume of ~15–20% annually for patients with untreated CLN2 Batten disease 138 .…”
Section: Advances In Therapy Developmentcontrasting
confidence: 55%
“…28 Although MRI is not sensitive or specific f or early diagnosis, it is an excellent tool to objectively monitor the progression of brain changes, particularly with ad vances in resolution and processing, and neuro imaging techniques such as diffusion tensor imaging allow assess ment of disorganisation of white matter tracts and atrophy. Two prospective studies 28,29 in patients with CLN2 disease have shown that the loss of cortical grey matter volume with increasing age might be a sensitive biomarker to monitor disease progression.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…2,40 Atrophy of the cerebellum is variable but evident in the later stages of all NCLs. 28,29,43 Neuronal depletion in the retina commences in the photoreceptor outer segments, proceeding to the inner segments, nerve cell bodies, and ganglionic layer, and occurs early in CLN3 disease, 44,45 while other symptoms (eg, epilepsy) precede visual loss in other types of NCLs. 1,40 In all forms of NCLs lipopigment storage material accumulates in macro phages, neurons, and some somatic tissues, including vascular endothelial and smooth muscle cells.…”
Section: Pathologymentioning
confidence: 99%
“…All gray regions of the brain are affected by neuronal death, showing however differential patterns in the topography of neuronal loss, the rate of progression and the secondary involvement of the white matter. Selective neurodegeneration, targeting specific regions and particular cell populations, can be observed during the early stages of the disease, and the patterns of disease evolution can be monitored by neuroimaging studies (136)(137)(138)(139)(140). Whether these features reflect the genetic heterogeneity of the NCL is a matter to be investigated further.…”
Section: Pathology and Pathogenetic Mechanismsmentioning
confidence: 99%